(untitled) (Research, Society and Development, 2022)
The article presents results of research developed in the Postgraduate Program in Public Policies and Educational Management at UFSM. It aimed to understand how students of the institution’s undergraduate courses understand gender and sexualities, considering their role as future teachers. Based on a qualitative approach, an online questionnaire was used to collect data, distributed to students participating in the PIBID and Pedagogical Residency programs of the UFSM degree courses. To understand the data, Discourse Analysis was chosen, from which some elements were listed for analysis: the discourses produced by the PPC’s of the degrees; the speeches present in the speeches of the subjects regarding the relevance of the theme for the teaching performance, and also the relationship between training and practice in educational contexts. It was noticed that, despite some degrees offering courses on the subject in their curricula, there are gaps in training. It is necessary to consider the relevance of inserting the theme for the promotion of critical subjects, who seek equity and free from prejudice.